Portable and Cost-Effective Handheld Ultrasound System Utilizing FPGA-Based Synthetic Aperture Imaging - Wenping Wang; Ziliang Feng (IEEE Open Journal of Nanotechnology)
The handheld ultrasound has been widely applied in various clinical applications due to its high portability and cost-effectiveness advantages. The smaller hardware architecture can expand its range of application scenarios. However, miniaturized ultrasound devices face the challenges in terms of image quality, frame rate, and power consumption. The achievement of high-quality and high-frame-rate imaging depends on numerous channels and higher pulse repetition frequency (PRF) at the cost of power consumption. The proposed work aims to design a field-programmable gate array (FPGA)-based prototype with synthetic aperture method for portable and cost-effective handheld ultrasound system. The prototype supports 8 transmit and receive channels and forms up to 8 synthetic apertures. In addition, to optimize the FPGA resources, the auto delay calculation and segmented apodizations are employed for 4 parallel beamforming lines. To evaluate the performance of our proposed prototype, scan sequences of B-mode, C-mode, and D-mode are implemented for image construction. The results show that the proposed prototype can provide a lateral resolution of 0.30 mm, a contrast-to-noise ratio (CNR) of 7.58 dB, and a frame rate of 22 frames per second (FPS) in dual-mode imaging. Moreover, it is remarkable that the memory and logic resources in the FPGA (EP4CE55) account for 73.7% and 66.2%, respectively, which makes the FPGA's power consumption only about 530 mW. The proposed prototype is suitable for handheld and other miniaturized ultrasound imaging systems.